Fullerenes : Principles and Applications. - Langa De La Puente, Fernando; Nierengarten, Jean-Francois; O'Brien, Paul; Craighead, Harold; Kroto, Harry (Royal Society of Chemistry, The, Ingram Publisher Services [distributor], 2011)
Annotation The discovery of caged carbon structures, in 1985, established a whole new field of carbon chemistry. Unlike graphite and diamond, these structures known as fullerenes are finite in structure and are relevant to a wide variety of fields including supramolecular assemblies, nanostructures, optoelectronic devices and a whole range of biological activities. Fullerenes: Principles and Applications discusses all aspects of this exciting field. Sections include: the basic principles for the chemical reactivity of fullerenes, electrochemistry, light induced processes, fullerenes for material sciences, fullerenes and solar cells, biological applications and multifunctional carbon nanotube materials. Written by leading experts in the field the book summarises the basic principles of fullerene chemistry but also highlights some of the most remarkable advances that have occurred in recent years. The second edition of this exciting title has been fully updated and revised. New sections cover several new topics including the basic principles for the chemical reactivity of fullerenes, electrochemistry, light induced processes, fullerenes for material sciences, fullerenes and solar cells, biological applications and multifunctional carbon nanotube materials. Written by leading experts in the field the second edition summarises the basic principles of fullerene chemistry but also highlights some of the most remarkable advances that have occurred in recent years. This book will appeal to researchers in both academia and industry.
Keywords: Fullerenes.; elektronické knihy; electronic books